2018
DOI: 10.1111/ijfs.13834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infrared radiation drying and heat pump drying combined with tempering on the quality of long‐grain paddy rice

Abstract: The objectives of this study were to study the effects of two drying methods, infrared radiation (IR) drying and heat pump (HP) drying, combined with tempering in the glassy state on the quality of long‐grain paddies (O. sativa L. subsp. indica) and the effects of intermittent ratios (δ = 0, 1, 2, 3, 4) on the milling properties and texture profiles of the paddies. The tempering temperature was set at 60 °C, according to the glass transition temperature (Tg) of the paddy rice, which was determined to be 58 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 38 publications
4
22
0
1
Order By: Relevance
“…A study performed by Zhou et al (2018) supported that the grain exposure time to IR heating reduces the HRY. Tempering drying was performed with different intermittent ratios, and the HRY increased when larger intermittent ratios were used because in this case were less grain exposed time to radiation.…”
Section: Drying Kineticsmentioning
confidence: 97%
See 1 more Smart Citation
“…A study performed by Zhou et al (2018) supported that the grain exposure time to IR heating reduces the HRY. Tempering drying was performed with different intermittent ratios, and the HRY increased when larger intermittent ratios were used because in this case were less grain exposed time to radiation.…”
Section: Drying Kineticsmentioning
confidence: 97%
“…The majority of the studies found in the literature with IR drying and heating treatments were carried out in medium grain rice (Bualuang et al, 2012;Das, Das, & Bal, 2004;Das, Das, & Bal, 2009;Ding, Khir, Pan, Zhang, et al, 2015;Ding, Khir, Pan, Zhao, et al, 2015;Ding et al, 2018;Khir, Pan, Salim, Hartsough, & Mohamedc, 2011;Pan et al, 2008;Wang, Khir, Pan, & Yuan, 2017) and little information is found for long grain rice (Likitrattanaporn & Noomhorm, 2011;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The relative peak areas of the less- and more-mobile water fractions in each sample are displayed in Table S1 . The T 2 relaxation time in the curves reflects the chemical environment encountered by protons in the sample, and the relaxation times of T 21 , T 22 , and T 23 can be considered to be related to bound water, nonflowing water, and free water in paddy rice, respectively [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…La práctica que se ajusta al secado en bajas temperaturas es la liofilización, es donde se consiguen productos de buena calidad; pero con tiempos muy prolongados en el proceso, mayores a los del secado de aire caliente [4,5]. El secado es un paso complicado en el que causa una transmisión sincrónica de materia y de energía, la modelización forma un instrumento necesario para estudiar estos métodos y la atribución de los escenarios de manipulación [6], [7]; la transmisión de los compuestos dentro del alimento se promueve exclusivamente por las subidas de humedad, a lo que se llama mecanismo difusivo [8]. Así, la modelización de las cinéticas de secado consiente lograr medidas como la difusividad segura del producto, cuantificación básica para estimular la perfección el proceso de secado [9].…”
Section: Introductionunclassified